Cytotoxicity of certain seed extracts against Artemia fransiscana (Bangladesh Journal of Zoology, 2015)
The chloroform and methanolic extracts of seed coat and seed kernel of Mucuna pruriens, Terminalia. bellirica, Syzygium cumini and Myristica fragrans were tested against the brine shrimp, Artemia fransiscana nauplii for mortality at 24h post exposure. All the test extracts were found to be effective. The toxicity of the chloroform extracts of seed coat could be arranged in the order: T. bellirica > M. pruriens > S. cumini > M. fragrans. In case of seed kernel extracts (chloroform) the results could be arranged in the following order: S. cumini > M. fragrans > T. bellirica > M. pruriens. For methanolic extracts of seed coat and seed kernel the results could be arranged in the following order: M. fragrans > T. bellirica > S. cumini > M. pruriens, and T. bellirica > S. cumini > M. fragrans > M. pruriens. The brine shrimp bioassay is a simple, reliable and convenient method for the assessment of bioactivity of medicinal plants and lends support for their use in traditional medicine.Bangladesh J. Zool. 42(2): 133-139, 2014